Efficacy of Benson's relaxation technique on anxiety and depression among patients undergoing hemodialysis: a systematic review - Abu Maloh, Haya Ibrahim Ali; Soh, Kim Lam; AbuRuz, Mohannad Eid; Chong, Seng Choi; Ismail, Siti Irma Fadhilah; Soh, Kim Geok; Abu Maloh, Dima Ibrahim (Sage, 2021)
This study aimed to evaluate the efficacy of Benson’s relaxation technique on anxiety and depression among patients undergoing hemodialysis. A systematic review of randomized controlled trials was conducted. Searching databases included EBSCO Host, PubMed, ProQuest, Science Direct, Sage Journals, Ovid, and Google Scholar from January 2000 to September 2020. Five randomized controlled trials were identified. Findings revealed a statistically significant decrease in anxiety score. Concerning depression; one RCT showed a statistically significant decrease and two RCTs revealed a non-significant difference in depression level. The overall quality of the RCTs was not high. Despite that the RCTs showed benefits of BRT in managing anxiety. However, this is not the same for depression. The lack of high-quality scientific evidence supporting its retinue use indicates that additional well designed randomized controlled trials in multiple countries are warranted to support the efficacy of Benson’s relaxation technique on anxiety and depression among patients undergoing hemodialysis.